Indonesia Rejoining OPEC: Dynamics of the Oil Importer and Exporter Countries - Badaruddin, Muhammad (JAS (Journal of ASEAN Studies), 2015)
Reactivation of Indonesiaâ€™s full membership to the Organization of the Petroleum Exporting Countries (OPEC) triggered discussion surrounding global petroleum governance. The country which decided to suspend its full membership at the end of 2008, currently labelled as net oil importer. However, in OPEC terms Indonesia never really left, instead of the organization termed it as a "suspensionâ€. Departing from the abovementioned context and perspectives, purpose of this essay is to answer the questions about the significance of the Indonesiaâ€™s membership reactivation to OPEC, and the strategic context of the reactivation in the current global oil market. In answering these questions, this article draws the dynamics of the relation of Indonesia and OPEC through the history in the first part and explores Indonesiaâ€™s interests in rejoining OPEC in the second one. In the third part, this essay will explore the possible benefit for OPEC as an organization as well as for its member countries could achieve by approving Indonesiaâ€™s request to reactivate its membership, despite its status as a net oil importer.